Antimicrobial Impact of Different Air-Polishing Powders in a Subgingival Biofilm Model - Johannes-Simon Wenzler; Felix Krause; Sarah Böcher; Wolfgang Falk; Axel Birkenmaier; Georg Conrads; Andreas Braun (MDPI AG, 2021)
Subgingival air-polishing devices (SAPD) can reduce bacterial biofilms and thus support periodontal healing. The authors of this study evaluated the effectiveness of the glycine-based and trehalose-based air-polishing powders in removing pathogenic bacteria in a subgingival biofilm model. We treated 56 subgingival pockets in porcine jaws with SAPD. Subgingival air polishing was performed in three groups of 13 pockets each: I, glycine-based powder; II, trehalose-based powder; and III, water alone. Another group (IV) served as untreated controls. Prior to air polishing, inoculated titanium bars were inserted into the pockets containing periopathogenic bacteria such as Porphyromonas gingivalis and Tannerella forsythia. Remaining bacteria were evaluated using real-time PCR. The numbers of remaining bacteria depended on the treatment procedure, with the lowest number of total bacteria in group I (median: 1.96 × 106 CFU; min: 1.46 × 105; max: 9.30 × 106). Both polishing powders in groups I and II (median: 1.36 × 107 CFU; min: 5.22 × 105; max: 7.50 × 107) showed a statistically significantly lower total bacterial load in comparison to both group IV (median: 2.02 × 108 CFU; min: 5.14 × 107; max: 4.51 × 108; p < 0.05) and group III (median: 4.58 × 107 CFU; min: 2.00 × 106; max: 3.06 × 108; p < 0.05). Both subgingival air-polishing powders investigated can reduce periopathogenic bacteria and thus support antimicrobial therapy approaches in periodontal treatment regimens.